Model Pendistribusian Dana Zakat Infak Sedekah (Zis) Dalam Pemberdayaan Masyarakat Di Balai Kreatif Laz-da Rizki Jember - Faizatul Hikmah; Uswatun Hasanah; Faizzatul Zuhroh; Fauzan (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2023)
The distribution of zakat funds comprises both consumptive and productive zakat in addition to the former. The Lamiga (Family Nutrition Pond) and Seel For Charity projects are examples of effective zakat. Utilizing zakat is a way to make the most of it without diminishing its worth or utility, making it effective for achieving social good. The infaq and alms funds itself are distributed through the Creative Center's community empowerment program. The Creative Center, also known as bakre, is a platform for empowerment that supports the development of a sense of community, character, independence, and responsibility that influences the transformation of the country. There are 15 bakre now dispersed throughout Jember Regency. With the help of this creative hub, the locals will feel more empowered, independent, and creative, which will raise their standard of living. At this bakre, there are various activities, including Roda (empowering potential), Tasya (planting family vegetables), Tasjali (collecting used items and protecting the environment), Supermas (supporting the prosperity of the mosque), Mas Rangga (packing baskets for families), and Dasat (health conscious).